BEYOND TOURISM: HOW DIGITAL NOMADS DRIVE STRONGER LOCAL BUSINESS GROWTH IN URBAN BALI? - Gede Andika; Muhammad Williams Rahaditama; I Komang Mardika; Putu EviraKusuma Cahyadewi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Background: Digital nomadism in urban areas in Bali becomes more and more defined as the practice of nomads being economically embedded within the economy rather than tourists. Objective: In this regard, this research seeks to investigate the influence of digital nomadism on local business development in the case of the city of Bali by looking into how nomad presence translates into economic gains for the local community. Method: By adopting an explanatory design with a quantitative focus, data from a sample of 150 micro, small and medium enterprises (MSMEs) operating in Canggu, Ubud, and Denpasar were collected. OLS regression analysis is used in order to evaluate the influence of variables such as digital nomad intensity, professional interaction quality, business adaptation strategy, and customer engagement on local business growth. Results: Results suggest that digital nomad intensity has a positive impact on business growth, with customer engagement as a factor having the highest significance. Most importantly, the interaction effect shows that the economic influence is greatly enhanced through high-quality interactions and a well-adapted digitalization strategy, providing better results than tourist inflow. Conclusion: Relationship building and development of the organization’s internal competencies become key aspects of the economic translation of digital nomadism.